Surface Modification of Composite Coating for Marine Application: A Short Review - Aulia, Hafiz; Riastuti, Rini; Ramdhani, Rizal Tresna (National Research and Innovation Agency (BRIN), 2024)
Corrosion is one of the phenomena that affects the deterioration of materials in offshore applications. Marine corrosion is particularly aggressive, due to the high salt content and low electrical resistivity of seawater. Corrosion cannot be stopped completely, but the reaction can be slowed down. Applying coating is an effective and widely used method to protect metal surfaces from corrosion. Coatings act as a barrier between the metal and its environment, preventing or slowing down the corrosive processes. Pursuant to ISO 12944, the most commonly used generics for coating systems in marine service are alkyd, acrylic, ethyl silicate, epoxy, vinyl ester, polyurethane, polyaspartic, and polysiloxane. The latest innovations in marine coatings still use a layer-by-layer coating method (e.g. primer coats, intermediate coats, and top coats) depending on thickness. Marine structures exposed to the atmospheric zones are usually coated with one or two coats of epoxy. A slightly more costly system of one coat of zinc-rich primer, one coat of epoxy, and one coat of aliphatic polyurethane may provide better performance. Coating systems for the atmospheric zones are frequently used in the intertidal and splash zones. Immersion zones of marine structures are commonly coated with one or two coats of 100% solid epoxy or three coats of solvent-borne epoxy. A single polymer as a generic coating have limitations. Adding fillers is a common method to improve the properties of polymers to become a composite. In marine coatings, fillers are still limited to glass flakes and powder. Poor dispersion and agglomeration might reduce the effectiveness of fillers in the matrix, which decreases the adhesion properties. The fillers must be surface modification before the application. This review provides a comprehensive and critical review of the current research status of composite coatings that serve as candidates to be used in marine coating.